Sequential Organ Failure Assessment Score for Evaluating Organ Failure and Outcome of Severe Maternal Morbidity in Obstetric Intensive Care - Antonio Oliveira-Neto; Mary A. Parpinelli; Jose G. Cecatti; Joao P. Souza; Maria H. Sousa (The Scientific World Journal)
Objective. To evaluate the performance of Sequential Organ Failure Assessment (SOFA) score in cases of severe maternal morbidity (SMM). Design. Retrospective study of diagnostic validation. Setting. An obstetric intensive care unit (ICU) in Brazil. Population. 673 women with SMM. Main Outcome Measures. mortality and SOFA score. Methods. Organ failure was evaluated according to maximum score for each one of its six components. The total maximum SOFA score was calculated using the poorest result of each component, reflecting the maximum degree of alteration in systemic organ function. Results. highest total maximum SOFA score was associated with mortality, 12.06 ± 5.47 for women who died and 1.87 ± 2.56 for survivors. There was also a significant correlation between the number of failing organs and maternal mortality, ranging from 0.2% (no failure) to 85.7% (≥3 organs). Analysis of the area under the receiver operating characteristic (ROC) curve (AUC) confirmed the excellent performance of total maximum SOFA score for cases of SMM (AUC = 0.958). Conclusions. Total maximum SOFA score proved to be an effective tool for evaluating severity and estimating prognosis in cases of SMM. Maximum SOFA score may be used to conceptually define and stratify the degree of severity in cases of SMM.